A sexually dimorphic signature of activity-dependent BDNF signaling on the intrinsic excitability of pyramidal neurons in the prefrontal cortex - Ma, Kaijie; Zhang, Daoqi; McDaniel, Kylee; Webb, Maria; Newton, Samuel S.; Lee, Francis S.; Qin, Luye (Frontiers in Cellular Neuroscience, 2024)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders with strong genetic heterogeneity and more prevalent in males than females. We and others hypothesize that diminished activity-dependent neural signaling is a common molecular pathway dysregulated in ASD caused by diverse genetic mutations. Brain-derived neurotrophic factor (BDNF) is a key growth factor mediating activity-dependent neural signaling in the brain. A common single nucleotide polymorphism (SNP) in the pro-domain of the human BDNF gene that leads to a methionine (Met) substitution for valine (Val) at codon 66 (Val66Met) significantly decreases activity-dependent BDNF release without affecting basal BDNF secretion. By using mice with genetic knock-in of this human BDNF methionine (Met) allele, our previous studies have shown differential severity of autism-like social deficits in male and female BDNF +/Met mice. Pyramidal neurons are the principal neurons in the prefrontal cortex (PFC), a key brain region for social behaviors. Here, we investigated the impact of diminished activitydependent BDNF signaling on the intrinsic excitability of pyramidal neurons in the PFC. Surprisingly, diminished activity-dependent BDNF signaling significantly increased the intrinsic excitability of pyramidal neurons in male mice, but not in female mice. Notably, significantly decreased thresholds of action potentials were observed in male BDNF +/Met mice, but not in female BDNF +/Met mice.Voltage-clamp recordings revealed that the sodium current densities were significantly increased in the pyramidal neurons of male BDNF +/Met mice, which were mediated by increased transcriptional level of Scn2a encoding sodium channel NaV 1.2. Medium afterhyperpolarization (mAHP), another important parameter to determine intrinsic neuronal excitability, is strongly associated with neuronal firing frequency. Further, the amplitudes of mAHP were significantly decreased in male BDNF +/Met mice only, which were mediated by the downregulation of Kcnn2 encoding small conductance calciumactivated potassium channel 2 (SK2). This study reveals a sexually dimorphic signature of diminished activity-dependent BDNF signaling on the intrinsic neuronal excitability of pyramidal neurons in the PFC, which provides possible cellular and molecular mechanisms underpinning the sex differences in idiopathic ASD patients and human autism victims who carry BDNF Val66Met SNP.